Plasticity induced closure under variable amplitude loading in AlMgSi aluminum alloys - Borrego, L. F. P. (2017)
Fatigue crack propagation tests under peak overloads, as well as High-Low and Low-High block loading sequences have been performed in aluminum alloy specimens. The observed transient crack closure level is discussed in terms of loading sequence, load change magnitude and ΔK baseline levels. The crack closure level is compared with the crack growth transients. A good agreement between experimental and predicted crack growth rates is obtained when the partial crack closure effect is properly taken into account. Therefore, plasticity-induced crack closure plays an important role on the load interaction effects observed in aluminum alloys.